"The Dearest Freshness Deep Down Things"1: Environmental Justice and Mission in Ecumenical Perspective. (July 2016) - Sasongko, Nindyo
Abstract: The ecumenical movement has produced many documents on issues of the environment and justice, but many churches do not know how to translate these documents into concrete actions. In this study I argue that social issues such as poverty and injustice cannot be separated from human responses toward the whole of creation. The ecumenical churches need to revitalize their mission and, as such, the churches need to revision their doctrines that centre on the human being by instead placing creation at the centre. Thus, nature is not just a background to the drama of redemption from sin, but that which God loves and preserves. This article elaborates this thesis in three main parts: the integrality of the problem of injustice and human responses toward all of creation, how churches should revision some major doctrines to be more sensitive to the environment, and how churches translate these documents into actions in their own contexts.